A prospective, multi-institutional study of perioperative morbidities in the patients of renal cell carcinoma undergoing either open nephron sparing surgery or robotic nephron sparing surgery in fifty cases - Chandra, Mahesh; Wasnik, Seema; Karan, Shailesh (International Surgery Journal, 2019)
Background: Over the time, the nephron sparing surgery (NSS) has become ‘gold standard’ for treatment of T1a stage renal cell carcinoma (RCC) which saves precious renal tissue. We assessed and compared perioperative morbidities associated with open (ONSS) and robotic nephron sparing surgery (RNSS) in patients of T1a and T1b staged renal cell carcinoma. Methods: This prospective study was carried out from April 2016 to March 2018. A total of fifty (n=50) RCC patients underwent open or robotic nephron sparing surgery. The demographic data and perioperative morbidities associated with both methods of NSS were recorded and comparison of parameters including warm-ischemia time (WIT), hospital stay, perioperative bleeding, impact of renal-pedicle clamping was made in T1a and T1b staged RCC patients. Results: The most common perioperative morbidity was blood-loss and 12% patients had ≥500 ml loss. Significantly less intraoperative blood-loss was observed in RNSS compared to ONSS with decreased blood transfusion (BT), which decreased significantly after renal-pedicle clamping prior to RCC resection. Even In perioperative period, the blood loss was significantly less in RNSS patients. However, the warm ischemia time (WIT) and hospital stay was longer in patients of RNSS compared to ONSS. The WIT was prolonged in T1b compared to T1a lesions, irrespective NSS methods. Conclusions: Although, the most common perioperative morbidity associated with NSS is blood-loss but RNSS had less perioperative morbidities compared to ONSS. The blood loss decreased significantly during intraoperative period after renal-pedicle clamping which resulted into decreased blood transfusion after NSS by either method.